Development of a Technical Guide for Project Based Learning on Chemical Literacy on Acid-Base Topic - Latifah Khairiyyah Fitri; Eka Yusmaita (Universitas Negeri Padang, 2022)
This study aims to develop a technical guide for project based learning based on chemical literacy on the topic of acid base learning that can be used to improve student’s chemical literacy skills and help student understand chemical concepts and be able to apply then un solving problems in daily life. This type of research is educational design research using the plomp model. The validity test was carried out by five validators including three chemistry lectures at the State University of Padang and two chemistry teachers at a SMAN Lima Puluh Kota and will be analysis of the validity results using Aiken’s V. the result of the analysis of content validity and construct validity can be categorized as valid.